'Guilty' pleasures are often worthwhile pleasures. Issue 1 (1st March 2019) - Cooke, Brandon
A guilty pleasure is something that affords pleasure while being held in low regard. Since there are more opportunities to experience worthwhile pleasures than one can experience in a finite life, it would be better to avoid guilty pleasures. Worse still, many guilty pleasures are thought to be corrupting in some way. In fact, many so-called guilty pleasures can contribute to a good life, because they are sources of pleasure and because they do not actually merit guilt. Taking pornography as a case study, I argue that in the absence of compelling evidence for its harmfulness, pornography can contribute to well-being by promoting autonomy, social recognition, knowledge and flourishing personal relationships. The case of pornography demonstrates an argumentative strategy for defending many so-called guilty pleasures as worthwhile elements of a flourishing life.